Community‐based observing for social–ecological science: lessons from the Arctic. (7th May 2018) - Griffith, David L; Alessa, Lilian; Kliskey, Andrew
Abstract : Environmental monitoring and observation by members of local communities have become increasingly common in the US and Canada over the past several decades. During the same period, social–ecological systems (SES) science has been developed to explain and predict human and environmental interactions, but empirical methods to generate matched social and ecological datasets are uncommon. Community‐based observing (CBO) methodologies were developed in the Arctic to allow for production of environmental data in a social context and are also well suited to provide empirical data for SES science. Community‐based observing networks and systems (CBONS) and community observer forums (COF) are methodologies developed from collaborations between community members, researchers, and government agencies. Here, we describe CBONS and COF methodologies, provide examples of their usage, and suggest ways in which they can benefit empirical SES science. We conclude by outlining efforts to expand the use of CBO to new knowledge and geographic domains.